PENGARUH KEPEMIMPINAN TRANSFORMASIONAL MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN (KOP “SAE” Pujon Malang Jawa Timur) - Rista Yuli Diah Saputri; Hadi Sunaryo (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThe purpose of this study was to describe transformational leadership, motivation, work culture and employee performance and to determine the effect of transformational leadership, motivation and work culture on employee performance partially and simultaneously.This research method uses quantitative methods. This type of research is explanatory research.The sample of this study was the